Corporate Governance, Industry Regulation and Efficiency of Retirement Benefit Schemes in Kenya - Namagwa, Sylvester Willys; Nyamute, Winnie; Okiro, Kennedy (Archives of Business Research, 2024)
The significance of retirement benefits arrangements has emerged in the wake of the waning traditional methods of caring for the elderly and the expected surge in the aging population, especially in developing economies. Despite the key role that retirement benefit arrangements play, there has been limited research on how corporate governance and industry regulation influence their efficiency. This study sets out to investigate the relationships among corporate governance, industry regulation and efficiency of retirement benefit schemes in Kenya. The study is grounded in several theoretical frameworks, including agency theory, stewardship theory, and financial distress theory. The study employs a quantitative research design, utilizing panel regression analysis to test the hypotheses. Data was collected from 896 observations across 128 retirement benefit schemes in Kenya, covering a seven-year period from 2015 to 2021. The results reveal that employee representatives on the board significantly and positively influence the efficiency of these schemes. Conversely, independent board members are found to have a negative effect on efficiency, suggesting potential challenges such as conflicts or slower decision-making processes. The study concludes that while corporate governance and industry regulation play significant roles in influencing the efficiency of retirement benefit schemes, their effects are interdependent and context specific. This study contributes to agency theory by providing empirical evidence that highlights the complexities of board composition in aligning the interests of managers and stakeholders within retirement benefit value-chain. The study reflects the importance of stakeholder-inclusive governance, particularly employee representation, as a means of aligning interests and enhancing organizational efficiency.